2021
DOI: 10.1302/1863-2548.15.200129
|View full text |Cite
|
Sign up to set email alerts
|

Arthrocentesis, arthroscopy or arthrotomy for septic knee arthritis in children: A systematic review

Abstract: Purpose Septic knee arthritis in children can be treated by arthrocentesis (articular needle aspiration) with or without irrigation, arthroscopy or arthrotomy followed by antibiotics. The objective of this systematic review was to identify the most effective drainage technique for septic arthritis of the knee in children. Methods The electronic PubMed, Embase and Cochrane databases were systematically searched for original articles that reported outcomes of arthrocentesis, arthroscopy or arthrotomy for septic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(49 reference statements)
0
14
0
1
Order By: Relevance
“…Recent systematic reviews showed a clear overview of the literature on drainage techniques for septic knee and hip arthritis in children[ 5 , 6 ]. It was concluded that knee arthroscopy might have a lower risk of additional drainage procedures as compared to arthrocentesis and arthrotomy in paediatric septic knee arthritis[ 5 ]. In septic hip arthritis, arthrocentesis and arthroscopic procedures may have a higher risk of additional drainage procedures in comparison with arthrotomy.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent systematic reviews showed a clear overview of the literature on drainage techniques for septic knee and hip arthritis in children[ 5 , 6 ]. It was concluded that knee arthroscopy might have a lower risk of additional drainage procedures as compared to arthrocentesis and arthrotomy in paediatric septic knee arthritis[ 5 ]. In septic hip arthritis, arthrocentesis and arthroscopic procedures may have a higher risk of additional drainage procedures in comparison with arthrotomy.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…Nonetheless, arthrotomy in septic hip arthritis might be associated with inferior outcomes on the long term[ 6 ]. However, the studies about the optimal drainage procedure of the several joints were diverse and the scientific quality was generally low[ 5 , 6 ].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 3 more Smart Citations